Scientific research in Nepal: Where we are - Shrestha, Bharat B. (Himalayan Journal of Sciences, 2006)
Lack of big funds is not the primary constraint in development of science and technology in Nepal. More important and subtle factors – lack of exchange of information between researchers; lack of co-operation and unhealthy competition between professors and among big institutions (although co-operation is essential for integrated study); data manipulation which prevails from beginners to some established researchers; and professors, the highly expert people in university, being enticed away from their research activity by private teaching institutes. Himalayan Journal of Sciences 1(1): 8-9, 2003 The full text is of this article is available at the Himalayan Journal of Sciences website